2021
DOI: 10.34293/education.v9is1-may.4002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reading Strategies Instruction on EFL Learners’ Reading Performances

Abstract: This study, using pretest-intervention-posttest, investigated whether instructing English as a foreign language (EFL) learners’ in the use of reading strategies when they read English passages affects their English reading performances. The participants were 51 Turkish learners of English, who were at elementary level of language proficiency,based on the results of the Oxford Quick Placement Test. The whole treatment/control period lasted for 20 sessions during 10 weeks on a Reading course. The experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among the most prevalent reading techniques employed by university students are: skimming, which entails skimming a book to gain a basic understanding of its content, organisation, and important elements (Gulo, 2020); scanning, which involves searching a text for specific information or features, such as keywords, headers, and statistics (Late & Kumpulainen, 2022); critical reading, a reading skill that focuses on studying the text, assessing its arguments and evidence, and challenging assumptions or prejudices (Aghajani & Gholamrezapour, 2019); collaborative reading, which prioritizes discussing the topic with peers or a study group, exchanging opinions, and posing questions to increase comprehension and perspective (Adachi & Kashihara , 2019); and also reflective reading, which is a technique that relates personal experiences or past knowledge to the text and linking new information to old knowledge (Coiro, 2020). These are only five among many more reading strategies which have been adopted, adapted, integrated, and revolutionized by many researchers and educators worldwide (Valizadeh, 2021).…”
Section: Reading Strategiesmentioning
confidence: 99%
“…Among the most prevalent reading techniques employed by university students are: skimming, which entails skimming a book to gain a basic understanding of its content, organisation, and important elements (Gulo, 2020); scanning, which involves searching a text for specific information or features, such as keywords, headers, and statistics (Late & Kumpulainen, 2022); critical reading, a reading skill that focuses on studying the text, assessing its arguments and evidence, and challenging assumptions or prejudices (Aghajani & Gholamrezapour, 2019); collaborative reading, which prioritizes discussing the topic with peers or a study group, exchanging opinions, and posing questions to increase comprehension and perspective (Adachi & Kashihara , 2019); and also reflective reading, which is a technique that relates personal experiences or past knowledge to the text and linking new information to old knowledge (Coiro, 2020). These are only five among many more reading strategies which have been adopted, adapted, integrated, and revolutionized by many researchers and educators worldwide (Valizadeh, 2021).…”
Section: Reading Strategiesmentioning
confidence: 99%
“…The OECD report indicated that Malaysia ranked much lower than her ASEAN counterparts, Singapore and Thailand. There are many studies that show how LLS could enhance reading skills (Almutairi, 2018;Habok & Magyat, 2019;Amin, 2019;Baba & Affendi, 2020;Banditvilai, 2020;Valizadeh, 2021). Therefore, teachers should provide clear instruction to students on the use of LLS in their reading.…”
Section: Introductionmentioning
confidence: 99%